2009
DOI: 10.1016/j.jvs.2009.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of carotid angioplasty and stenting for radiation-associated carotid artery stenosis

Abstract: This study suggests that the durability of CAS and the characteristics of captured embolic particles are not altered by a history of neck XRT. This supports the safety and efficacy of CAS for the treatment of patients with a history of neck XRT. Prior neck XRT may predispose the patient to the de novo development of stenoses at locations that were not previously treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 33 publications
2
24
1
Order By: Relevance
“…[9] Regarding baseline preoperative characteristics and comorbidities between the XRT and non-XRT patients, one prior study showed no difference in age, gender, hypertension, DM, dyslipidemia, smoking, chronic kidney disease, chronic obstructive pulmonary disease, coronary artery disease, and heart failure, [9] and another showed differences only with respect to hypertension and gender. [10] This is in contradistinction to our findings where the XRT patients were significantly younger in age compared to the non-XRT patients. The epidemiology of NPC, oral and oropharyngeal cancer is quite different in Taiwan compared with the West, [4,5] and the median age of diagnosis is significantly lower than in the West.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…[9] Regarding baseline preoperative characteristics and comorbidities between the XRT and non-XRT patients, one prior study showed no difference in age, gender, hypertension, DM, dyslipidemia, smoking, chronic kidney disease, chronic obstructive pulmonary disease, coronary artery disease, and heart failure, [9] and another showed differences only with respect to hypertension and gender. [10] This is in contradistinction to our findings where the XRT patients were significantly younger in age compared to the non-XRT patients. The epidemiology of NPC, oral and oropharyngeal cancer is quite different in Taiwan compared with the West, [4,5] and the median age of diagnosis is significantly lower than in the West.…”
Section: Discussioncontrasting
confidence: 90%
“…In addition, there were significantly fewer patients with CAD, hypertension, hyperlipidemia, DM, and chronic kidney disease in our XRT group, and this finding differed from similar studies reported in the Western literature. [9,10] The perioperative complications and primary outcomes, all causes of mortality, ipsilateral recurrent stroke, and MACE, did not significantly differ between the XRT and non-XRT patients, as noted previously. [9,10] However, a significantly higher restenosis rate was observed in our XRT patients, which correlated with previous studies.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…If the angiography reveals that residual stenosis is <30% after the stenting, aboral sacculus expansion would generally not be recommended. This is because the stent mesh would cut the plaque during the aboral sacculus expansion, which might cause the falling of a large number of plaques (Sadek et al, 2009). Moreover, the memory effect of the stent would still be able to slowly expand the main responsible vessels after self-expanding.…”
Section: Discussionmentioning
confidence: 99%